Sensing Pico‐Newton Plasmonic Forces and Jerks of LSPR Biochips Using Simple UV‐Visible Spectroscopy - Bhalla, Nikhil (Advanced Physics Research, 2025)
Localized surface plasmon resonances (LSPRs) involve the oscillation of free electrons, leading to the maximum absorption of light by nanostructures at a specific wavelength. This absorption generates an action force exerted by the light on the nanostructures, with a corresponding reaction force—equal in magnitude but opposite in direction—arising from the plasmonic resonances. Additionally, the optical force exerted by light on nanostructures results in jerks or changes in its reaction force over time as it interacts with light. Through mathematical modeling, the reaction forces and jerks on large‐area LSPR chips are determined using basic absorbance and reflection measurements performed with UV‐Visible spectroscopy on gold nanomushrooms. The system tested, immunoglobulin G (IgG) antibody and its complementary antibody complex, revealed forces of 6 and 6.26 pN respectively. These main findings and especially the equations for reaction force and jerk, enhance our understanding of absorbance and reflection spectra obtained from UV‐Visible spectroscopy. The developed model can be applied to analyze light‐induced forces experienced by micro/nano/bio material systems using simple UV‐Visible spectroscopy techniques. The figure represents the interaction of light interaction with a nanostructured plasmonic system. Incident light excites localized surface plasmon resonance (LSPR) and induces radiation forces on the nanostructures, as illustrated by the force vectors.